2015
DOI: 10.1053/j.gastro.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Lysophosphatidylcholine Acyltransferase 3 Reduces Plasma Levels of Lipids by Reducing Lipid Absorption in Mice

Abstract: BACKGROUND & AIMS Phosphatidylcholines (PCs) are structural and functional constituents of cell membranes. The activity of acyltransferase (LPCAT) is required for addition of polyunsaturated fatty acids to the sn-2 position of PCs, and is therefore required to maintain cell membrane structure and function. LPCAT3 is the most abundant isoform of LPCAT in the small intestine and liver—are important sites of plasma lipoprotein metabolism. We investigated the effects of Lpcat3 disruption on lipid metabolism in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…One explanation could be due to the compensation of other Lpcats. Indeed, we previously reported that global Lpcat3 deficiency causes about 90% reduction of total Lpcat activity in the small intestine, whereas the deficiency only causes about a 70% reduction of total activity in the liver (11). We confirmed this phenomenon in this study (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…One explanation could be due to the compensation of other Lpcats. Indeed, we previously reported that global Lpcat3 deficiency causes about 90% reduction of total Lpcat activity in the small intestine, whereas the deficiency only causes about a 70% reduction of total activity in the liver (11). We confirmed this phenomenon in this study (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…However, the same group recently reported that Lpcat3 deficiency in the liver does not affect the expression of ER stress markers (9). We also recently reported that global Lpcat3 deficiency has no impact on ER stress (11). In this study, we again measured the expression of ER stress markers in the Lpcat3-deficient small intestine and found that the deficiency attenuated (rather than enhanced) the expression of PERK and IRE-1␣ (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The reacylation step is catalyzed by lysophosphatidylcholine acyltransferase (LPCAT), which adds the PUFA at the sn-2 position of PC. Lpcat3 knockout mice die shortly after birth and when rescued by supplementing their diet with phosphatidylcholine, they display reduced lipid absorption and lower expression levels of Nieman-Pick C1-like 1 (NPC1L1), CD36, and FA transport protein 4 (FATP4) (88). Intestine specific Lpcat3 deficiency leads to a selective defect in the incorporation of the EFAs linoleate and arachidonate into phospholipids changing the biophysical properties of the enterocyte membranes (62,164).…”
Section: Fa Uptake and Processing By Enterocytesmentioning
confidence: 99%